Szczurojorczycy : (podsluchowisko) - Redlinski, Edward (Warszawa : Polska Oficyna Wydawnicza "BGW", 1997)
A contemporary novel about Poles living in New York City.
Poprzedni tytul: Szczuropolacy.
Keywords: New York (N.Y.) -- Fiction